A Neonatal Case With Perinatal Lethal Gaucher Disease Associated With Missense G234E and H413P Heterozygous Mutations - Wei, Meili; Han, Aiqin; Wei, Liping; Ma, Liji (Frontiers in Pediatrics, 2019)
Perinatal lethal Gaucher disease (PLGD), a particular and serious form of type 2 Gaucher disease (GD), often causes lethality in utero or death within hours after birth. The typical clinical manifestations include non-immune hydrops fetalis (NIHF), premature birth, fetal growth restriction, fetal intrauterine death, or neonatal distress and rapid death after birth. Here, we present a premature neonate with GD whose main clinical manifestations included intrauterine growth retardation, anasarca, facial dysmorphia, ichthyosis, respiratory distress, hepatosplenomegaly, joint contractures, myoclonus, refractory thrombocytopenia, anemia, elevated levels of liver enzymes, bile acid and direct bilirubin, cholestasis, pulmonary hypoplasia, intracranial hemorrhage, and abnormal electroencephalogram. The activity of β- glucocerebrosidase was 0 in the peripheral white blood cells of the neonate. The sequencing analysis identified the presence of missense G234E and H413P heterozygous mutations in glucerebrosidase (GBA) exon 7 and 10, with the latter first observed to be associated with PLGD. This infant died at 73 days of age.